The effect of gastric fundus radiation dose on postoperative anastomotic leakage in esophageal cancer - Kundel, Yulia; Kurman, Noga; Sulimani, Omri; Gavrielli, Shlomo; Nachalon, Yuval; Moore, Assaf; Kashtan, Hanoch; Fenig, Eyal; Brenner, Baruch; Popovtzer, Aron; Fredman, Elisha (Frontiers in Oncology, 2023)
Introduction Standard of care treatment for locally advanced esophageal carcinoma (LAEC) includes neoadjuvant chemoradiotherapy followed by esophagectomy. A potentially catastrophic surgical complication is development of a postoperative anastomotic leak. To date, the association with radiation dose exposure had been inconclusive. We examined the correlation between radiation exposure to the gastric fundus and risk of postoperative leakage using contemporary radiation doses and fractionation. Methods 69 consecutive patients with LAEC who underwent neoadjuvant chemoradiotherapy followed by esophagectomy in our tertiary center were prospectively followed (median 27 months). Neoadjuvant regimen included 50.4 Gy in 28 fractions with 5-fluorouracil and cisplatin and 41.4 Gy in 23 fractions with carboplatin and paclitaxel. The gastric fundus was contoured and dosimetric and radiation technique parameters were retrospectively evaluated. Results 71% and 29% of patients had esophageal and gastroesophageal junction (GEJ) tumors, respectively. Fourteen patients (20.3%) experienced anastomotic leaks within a median of 2 days post-op, 78.6% of whom had lower third esophagus or GEJ primaries. Mean and minimum fundus dose did not significantly differ between those with and without leakage (p=0.42, p=0.51). Mean fundus V25, V30, and V35 doses were numerically but not statistically higher in those with anastomotic leak (p=0.58; p=0.39; p=0.30). No correlation with incidence of leakage was seen between 3D vs IMRT treatment modalities. Conclusions In our comparatively large prospectively collected series of patients treated for LAEC, radiation dose to the gastric fundus during neoadjuvant combination therapy prior to surgery did not correlate with the risk of postoperative anastomotic leak.